Engineering Geology Aspects Relating to Preliminary Damsite Investigations on the Nelson River, Manitoba - Piteau, Douglas R. (Canadian Geotechnical Journal, 1972)
Engineering geology aspects of the preliminary investigation of nine alternative damsites along the lower reach of the Nelson River between Split Lake and Hudson Bay, Manitoba, Canada are described.Glacial drift, comprising mainly ablation and basal till, almost completely blankets the area, and active slope failures are common. The western part of the area is underlain by Precambrian rocks, which in the eastern part of the area are overlain by Paleozoic dolomitic limestone. Discontinuous permafrost conditions particularly presented some interesting terrain and investigation problems.The engineering geology studies included airphoto interpretation, both reconnaissance and detail geologic mapping, trenching, drilling, seismic-refraction surveys, river soundings, and ground surveys.